Acoustic Characterization and Enhanced Ultrasound Imaging of Long‐Circulating Lipid‐Coated Microbubbles. (11th November 2017) - Li, Hongbo; Yang, Yanye; Zhang, Meimei; Yin, Liping; Tu, Juan; Guo, Xiasheng; Zhang, Dong
Abstract : Objectives: A long‐circulating lipid‐coated ultrasound (US) contrast agent was fabricated to achieve a longer wash‐out time and gain more resistance against higher–mechanical index sonication. Systemic physical, acoustic, and in vivo imaging experiments were performed to better understand the underlying mechanism enabling the improvement of contrast agent performance by adjusting the physical and acoustic properties of contrast agent microbubbles. Methods: By simply altering the gas core, a kind of US contrast agent microbubble was synthesized with a similar lipid‐coating shell as SonoVue microbubbles (Bracco SpA, Milan, Italy) to achieve a longer wash‐out time and higher inertial cavitation threshold. To bridge the structure‐performance relationship of the synthesized microbubbles, the imaging performance of the microbubbles was assessed in vivo with SonoVue as a control group. The size distribution and inertial cavitation threshold of the synthesized microbubbles were characterized, and the shell parameters of the microbubbles were determined by acoustic attenuation measurements. All of the measurements were compared with SonoVue microbubbles. Results: The synthesized microbubbles had a spherical shape, a smooth, consistent membrane, and a uniform distribution, with an average diameter of 1.484 μm. According to the measured attenuation curve, the synthesized microbubbles resonated at around 2.8 MHz. Although the bubble's shell elasticity (0.2 ± 0.09 N/m) was comparable with SonoVue, it had relatively greater viscosity and inertial cavitation because of the different gas core. Imaging studies showed that the synthesized microbubbles had a longer circulation time and a better chance of fighting against rapid collapse than SonoVue. Conclusions: Nano/micrometer long‐circulating lipid‐coated microbubbles could be fabricated by simply altering the core composition of SonoVue microbubbles with a higher–molecular weight gas. The smaller diameter and higher inertial cavitation threshold of the synthesized microbubbles might make it easier to access deep‐seated organs and give prolonged imaging enhancement in the liver.